Biomechanical analysis of simultaneous distal and proximal radio-ulnar joint instability - Naoki Hayami (2020)
© 2020 The Authors Background: Simultaneous dislocation of the proximal and distal radio-ulnar joints without bony injuries has been reported, but the mechanism remains unclear. We investigated concurrent proximal and distal radio-ulnar joint instability after sequential sectioning of the annular ligament, triangular fibrocartilage complex, and quadrate ligament. Methods: We performed this biomechanical study with six fresh-frozen cadaveric upper extremities. Proximal and distal radio-ulnar joint displacement was measured using an electromagnetic tracking device during passive mobility testing with anterior, lateral, and posterior loads on the radial head with pronation, supination, and neutral rotation. Measurements were statistically analyzed using the generalized linear mixed model. Findings: Proximal radio-ulnar joint instability was significantly greater after sectioning of the annular (lateral: 1.4%, P < .05; posterior: 0.7%, P < .05) and quadrate (lateral: 43.7%, P < .05; posterior: 29.5%, P < .05) ligament. Distal radio-ulnar joint instability was significantly greater in every sequential stage (final stage: anterior: 24.1%, P < .05; lateral 21.0%, P < .05; posterior: 31.3%, P < .05). Finally, significant simultaneous instability of the joints was observed after sectioning of the annular ligament, triangular fibrocartilage complex, and quadrate ligament, and neutral rotation potentially induced gross instability. Interpretation: Our ligament injury model induced simultaneous proximal and distal radio-ulnar joint instability without bony or interosseous membrane injury, probably induced by severe soft tissue injury. Proximal radio-ulnar joint instability may influence distal radio-ulnar joint instability from pivoting of the interosseous membrane. Our findings will help surgeons evaluate the magnitude of soft tissue injury and plan surgery for patients with simultaneous proximal and distal radio-ulnar joint instability.